'You Always Need at Least Two Tones to Produce a Harmonious Sound': The Value of Arendt's Ideas on Friendship for Thinking in Social Psychology. (June 2022) - Zadeh, Sophie; Coultas, Clare
In this article, we focus on Arendt's ideas about the relationship between thinking, dialogue and friendship to make the argument that friendship, although undertheorised in its relationship to thinking in social psychology, is a productive concept that captures something important about the argumentative and dialogical character of thinking (both on one's own, and with other people). We work through Arendt's ideas and discuss them in relation to social psychological theorising to consider how the concept of friendship can deepen our understanding and analyses of the relationalities that underpin thinking. We specify that whilst thinking in existing social psychological accounts may be read as adversarial in nature (e.g. through a focus on its oppositional character), the relationship between thinking and friendship has been an important idea underlying the perspectives presented in such works. Distinguishing between thinking as friends and thinking in groups, we suggest that there may be something special about the role of friendship in thinking. We draw out this idea by turning to Arendt, and simultaneously use the work of social psychologists to reconsider aspects of The Life of the Mind, in which thinking is mostly conceptualised as a solitary activity.